The Use of A Read Along Application to Improve Students’ Pronunciation - Amia Windy Fajrina; Noor Anzali, Muhamad; Perdana, Purnama Rika (English Education, Linguistics, and Literature Journal, 2025)
This study aims to enhance students' English pronunciation skills through the use of the Read Along application. The research focused on seventh-grade students at SMPN 2 Cilegon during the 2023/2024 academic year. The participants were 34 students from class VII B. The methodology employed was Classroom Action Research (CAR) as developed by Kemmis and McTaggart, conducted in two cycles each consisting of planning, action, observation, and reflection. Data collection involved both qualitative and quantitative methods. Qualitative data was gathered using observation sheets, while quantitative data was obtained through tests. The application usefulness was hampered in cycle I initial test by problems like slow internet connectivity and low student participation. The first was for the students to open the application, which they did without any problems. However, only about 20% of students were able to grasp the second level's features. This was due to the students' inexperience with the technology of the application, which made it take longer for them to get used to. With an average score of 62.41, only 6 students (17.65%) passed the Minimum Completion Criteria (KKM). After resolving these issues, demonstrated significant improvements in the second test of cycle II, there was significant improvement, with 29 students (85.30%) meeting the Mastery Minimum Criteria (KKM) and an average score of 82.05. The study concludes that the Read Along application is effective in improving the English pronunciation of seventh-grade students at SMPN 2 Cilegon.